2018
DOI: 10.1021/acs.molpharmaceut.8b00469
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and Structural Dynamics of Imatinib within Biorelevant Colloids

Abstract: Solubilization of lipophilic drugs is essential for efficient uptake. We detail the solubilization of imatinib in simulated gastrointestinal fluids containing taurocholate (TC) and lecithin (L) and reflecting fasted versus fed states using NMR spectroscopy, X-ray diffractometry, transmission electron microscopy, and dynamic light scattering analysis. Imatinib concentration impacted colloidal geometries and molecular dynamics in a fasted state. At drug substance concentrations up to 250 μM, imatinib was mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…were absent in the DSC thermograms of both agglomerates confirming their amorphous character (Figure S34 -35). Similarly, Wiest et al found completely amorphous drug in their taurocholate micelle agglomerates [13]. To further probe this interesting effect of the hydrophilic corona, we synthesized two new A*-B-A triblock terpolymers with mixed hydrophilic blocks (for characterization, see Figure S10-S13, S18-S19, S23, S25 and Table S1), selecting the two best performing hydrophobic blocks, pBuOx and pPrOzi (for PTX and CUR, respectively).…”
Section: Synthesis and Formulation Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…were absent in the DSC thermograms of both agglomerates confirming their amorphous character (Figure S34 -35). Similarly, Wiest et al found completely amorphous drug in their taurocholate micelle agglomerates [13]. To further probe this interesting effect of the hydrophilic corona, we synthesized two new A*-B-A triblock terpolymers with mixed hydrophilic blocks (for characterization, see Figure S10-S13, S18-S19, S23, S25 and Table S1), selecting the two best performing hydrophobic blocks, pBuOx and pPrOzi (for PTX and CUR, respectively).…”
Section: Synthesis and Formulation Studiesmentioning
confidence: 88%
“…With respect to the morphology of PMs, Schulz et al and later Cao et al reported that increasing the drug feed can induce a morphology transition from worm or rod like structures to small spherical micelles or vesicles [5,11], while Lübtow et al reported micelle formation of A-B-A triblock copolymers triggered only by the presence of a hydrophobic guest molecule [12]. More recently, Wiest et al showed that increasing the imatinib concentration in taurocholate/lecithin micelles above 250 µM, not only caused morphology transition from vesicles (>110 nm) to micelles (<40 nm) but also lead to colloidal collapse because of the migration of drug from the core to the shell of the micelles [13]. PMs have been studied intensively for decades with respect to their physicochemical properties and general behavior in biological systems [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, after 30 days, the LC decreased to 3 and 10 wt%, respectively. In case of higher MT feed of 6, 8, and 10 g L −1 (Figure b) a dramatic decrease in the LC (30 to 3, 35 to 2, and 36 to 4 wt%, respectively) was observed within 24 h. It is becoming more and more evident that drug molecules can also coordinate with the micellar corona . This drug–corona interaction can enable to ultra‐high drug loading or lead to colloidal instability of the formulation .…”
Section: Resultsmentioning
confidence: 92%
“…However, the drug corona interaction can also affect the morphology, endocytosis, or prolong supersaturation . Interestingly, for the POx/POzi nanoformulations the drug was found fully amorphous in the precipitate, which also contains polymer . It therefore appears that the micelles agglomerate and precipitate with the still amorphous drug embedded.…”
Section: Resultsmentioning
confidence: 99%
“…[44] Previous studies relied on flux measurements of polymeric drug formulations across artificial membranes in combination with differential scanning calorimetry (DSC). [45] 1 H-and DOSY (diffusion ordered spectroscopy) NMR spectroscopy were also identified as suitable tools in the investigation of drug loaded surfactant colloids in FaSSIF [28,46] or lipid free bile salt solutions. [47,48] Both of these NMR spectroscopic studies focus on either the drug molecule or the polymeric carrier material, while it is to be expected that the individual drug can also change the behaviour of the polymer in biorelevant media and vice versa.…”
Section: Introductionmentioning
confidence: 99%